2020
DOI: 10.1111/ipd.12614
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of parental report of dental pain and discomfort in preschool children—The Dental Discomfort Questionnaire

Abstract: BackgroundPain is a major consequence of caries, which negatively impacts the quality of life of children and their families.AimTo analyse the parental report of dental pain and discomfort in preschool children, and to identify clinical and sociodemographic factors associated.DesignThis cross‐sectional study involved 375 four‐ and five‐year‐old preschoolers enrolled in the city of Campo Magro public school system, along with their parents and caregivers. Parents/caregivers answered the Brazilian version of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…We observed that children living in an unfavorable socioeconomic environment did experience more postoperative pain and were more likely to receive analgesics. The impact of socioeconomic status on pain was previously described (Dorner et al, 2011;Felipak et al, 2020). Subjects living in less affluent socioeconomic areas reported higher prevalence of pain compared to others.…”
Section: Discussionmentioning
confidence: 91%
“…We observed that children living in an unfavorable socioeconomic environment did experience more postoperative pain and were more likely to receive analgesics. The impact of socioeconomic status on pain was previously described (Dorner et al, 2011;Felipak et al, 2020). Subjects living in less affluent socioeconomic areas reported higher prevalence of pain compared to others.…”
Section: Discussionmentioning
confidence: 91%
“…Unfortunately, two children were absent on the days scheduled for the clinical examinations. Thus, the final sample was composed of 376 preschoolers [2].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the occurrence of dental pain/discomfort impacts the family routine [5,24]. Studies that used the same assessment tool for this outcome also found an association between higher scores and the prevalence/severity of dental caries [2,25,26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations